2023
DOI: 10.3389/fmed.2023.1187163
|View full text |Cite
|
Sign up to set email alerts
|

ME/CFS and Long COVID share similar symptoms and biological abnormalities: road map to the literature

Abstract: Some patients remain unwell for months after “recovering” from acute COVID-19. They develop persistent fatigue, cognitive problems, headaches, disrupted sleep, myalgias and arthralgias, post-exertional malaise, orthostatic intolerance and other symptoms that greatly interfere with their ability to function and that can leave some people housebound and disabled. The illness (Long COVID) is similar to myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) as well as to persisting illnesses that can follow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 557 publications
(244 reference statements)
1
65
0
Order By: Relevance
“…Patients with ME/CFS may also present with fluctuations in severity of the disease akin to MS where symptoms rise and fall through cycles of relapse and remission . Onset or exacerbation of ME/CFS symptoms may be triggered as well by factors including (1) infection (viral and bacterial), (2) diet, (3) hormonal changes, (4) age, (5) environment, and (6) drug induction. , Molecular mimicry has also been proposed to induce autoimmunity in ME/CFS where viruses present infectious material such as peptides that have similar residue sequences as the host antigen(s); these foreign agents, which may cause an autoimmune response, include, for example, herpes 6, Epstein-Bar, and corona virus 229E. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ME/CFS may also present with fluctuations in severity of the disease akin to MS where symptoms rise and fall through cycles of relapse and remission . Onset or exacerbation of ME/CFS symptoms may be triggered as well by factors including (1) infection (viral and bacterial), (2) diet, (3) hormonal changes, (4) age, (5) environment, and (6) drug induction. , Molecular mimicry has also been proposed to induce autoimmunity in ME/CFS where viruses present infectious material such as peptides that have similar residue sequences as the host antigen(s); these foreign agents, which may cause an autoimmune response, include, for example, herpes 6, Epstein-Bar, and corona virus 229E. …”
Section: Resultsmentioning
confidence: 99%
“…Demyelination may also be a common denominator with ME/CFS where some patients experience symptoms of muscle pain and weakness as a results of diminished nerve function . To strengthen this idea, there are several reports of abnormal brain magnetic resonance imagining (MRI) studies in patients with ME/CFS. Based on images with white/gray matter hyperintensities and cerebral atrophy, Cook et al found that ME/CFS patients had a higher level of physical impairment (motor and cognitive functions) compared to patients with normal MRI scans. , Furthermore, there is a growing body of literature on COVID-related research postpandemic (e.g., Long-COVID) that makes a strong connection to ME/CFS; this suggests that COVID-19 infection may act as a precursor/trigger for ME/CFS. Demyelination in particular, which has been reported numerous times in cases of COVID-19, may play a larger role in neurological-related symptoms in patients recently diagnosed with ME/CFS.…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that viral illnesses can be a trigger for the onset of dysautonomia symptoms and this can lead to the development of long-term debilitating health problems such as long COVID and ME/CFS. 7,8 Identifying dysautonomia is primarily based on detailed history taking which can be done in any healthcare setting, looking for evidence of orthostatic intolerance, palpitations, temperature dysregulation, sweating problems, gastrointestinal symptoms, or sexual dysfunction. There are simple bedside/clinic tests that can be performed to look for evidence of pulse and BP changes in response to physiological demands such as standing and eating.…”
Section: A Global Need For More Awareness Of Dysautonomia In Postvira...mentioning
confidence: 99%
“…Common symptoms include cognitive blunting, also called "brain fog", chest pain, dyspnoea, fatigue, and sensory dysregulation, which often have a substantial impact on daily activities and quality of life, akin to myalgic encephalomyelitis/chronic fatigue syndrome. 4 A recent systematic review concluded that 45% of individuals experience diverse and unresolved symptoms 4 months after infection with SARS-CoV-2, irrespective of initial disease severity. 5 Chronic disease is also common.…”
Section: Introductionmentioning
confidence: 99%